1968
DOI: 10.1002/ardp.19683010410
|View full text |Cite
|
Sign up to set email alerts
|

Gyromitrin, das Gift der Frühjahrslorchel. 16. Mitt. über Pilzinhaltsstoffe

Abstract: Das Gift der Frühjahrslorchel wurde als N‐Methyl‐N‐formylhydrazon des Acetaldehyds aufgeklärt und synthetisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Only two fungal metabolites have been reported, agaritine from the cultivated mushroom Agaricus bisporus 14 and gyromitrin from the false morel Gyromitra esculenta. 15 As far as we know, elaiomycins B (2) and C (3) are the first natural occurring alkylhydrazides with therapeutic potential as shown by their inhibitory activity against clinically relevant enzymes.…”
mentioning
confidence: 99%
“…Only two fungal metabolites have been reported, agaritine from the cultivated mushroom Agaricus bisporus 14 and gyromitrin from the false morel Gyromitra esculenta. 15 As far as we know, elaiomycins B (2) and C (3) are the first natural occurring alkylhydrazides with therapeutic potential as shown by their inhibitory activity against clinically relevant enzymes.…”
mentioning
confidence: 99%
“…These chemicals are indeed powerful carcinogens, since they induced tumours in over two dozen tissues and organs of mice, hamsters and rats (Juih'asz et al, 1957;Biancifiori & Ribacchi, 1962;Morris et al, 1969;Druckrey, 1970;Toth, 1975Toth, , 1980. It is of interest to note here that the human population is exposed to about one half of these compounds in the form of drugs, agricultural herbicides or industrial chemicals, and as naturally occurring substances such as ingredients of edible mushrooms and tobacco (Levenberg, 1960;List & Luft, 1968;Merck Index, 1976;Schmeltz et al, 1977;LaRue, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigations were performed in this species with structural homologues of PFH, including N-methyl-N-formylhydrazine (MFR), N-ethyl-Nformylhydrazine and N-n-butyl-N-formylhydrazine (Totli & Nagel, 1978;Toth et al, 1979Toth & Nagel, 1908a. At the beginning, we selected MFH as the first step in otir inquiry because this chemical is an ingredient of the edible false morel mushroom Gyroinitra e8culenta (List & Luft, 1968; Schmidliii-Me'sza'ros, 1-975;Pyysalo & Niskaneii, 1977). It is known that the human poptilation is exposed to some extent, in certain areas, to this hazardous chemical (Miller, 1972).…”
mentioning
confidence: 99%
“…The findings in the first case clearly demonstrated the diminishing role of increased methyl substitution in the carcinogenic process [14], while in the latter it was concluded that additional experimentation was needed [15]Hydrazines, hydrazides and hydrazones are capable of inducing tumors in experimental laboratory animals in a large variety of tissues. To date, over 40 such com pounds are known to possess cancer-inducing abilities in mice, hamsters and rats [1,2], From an environ mental viewpoint, it appears important that the human population is exposed to approximately one-half of these chemicals in the form of drugs, agricultural her bicides, industrial agents [3] and naturally occurring substances, such as the ingredients of tobacco and edible mushrooms [4][5][6]16].…”
Section: Discussionmentioning
confidence: 99%
“…To date, over 40 such compounds were reported to produce neoplasms in the lungs, liver, kidneys, blood vessels, bladder, heart, intestines, gallbladder, bile ducts, stomach, lymphoreticular and nerve tissues, etc. of mice, hamsters and rats [1,2], A number of these compounds are used in industry, agriculture and medi cine [3] and some also occur in nature [4][5][6], There fore, from an environmental viewpoint, it appears pro mising to study their carcinogenic potential, since the human population is considerably exposed to a subs tantial number of these chemicals. Some of these stu dies are also aimed at revealing the possible relationship between chemical structure and tumor development at specific organ sites.…”
Section: Introductionmentioning
confidence: 99%